Diagnosis and Management of Latent Tuberculosis Infection: Updates - Swain, Satish; Kumar, Arvind; Vishwakarma, Vishal Kumar; Aayilliath K, Adarsh; Mittal, Ankit; Wig, Naveet (Infectious Disorders - Drug Targets, 2024)
India has the largest problem of tuberculosis (TB) infection globally (estimated at about 35-40 crores cases), and around 18-36 lakh develop active tuberculosis annually. Latent TB is defined as a state of persistent immune response to stimulation by Mycobacterium tuberculosis antigens with no evidence of clinically manifested active TB. The progression of a latent infection to active tuberculosis increases several-fold in children < 5 years of age and in people with some or the other form of an immunocompromising condition. Therefore, to cater to this gigantic problem of tuberculosis, it is necessary to have awareness about latent tuberculosis infection (LTBI) amongst clinicians and to prioritise its diagnosis and treatment in high-risk groups. India plans to end TB well before the deadline set by the World Health organisation (WHO). However, this can only be achieved with effective strategies targeting LTBI. Multiple treatment regimens have been approved for LTBI treatment, and all have comparable efficacy. The selection of one regimen over the other depends on various factors, such as availability, risk of adverse events, age, and drug interactions. Recently, the WHO, as well as the Revised National TB Control Programme (RNTCP), have updated their guidelines on TB preventive treatment in 2020 and 2021, respectively. This review has been especially prepared to acknowledge the differences in approach to LTBI in developed and developing countries.
Keywords: antiretroviral therapy